Pengaruh Brand Image dan Relationship Marketing terhadap Kepuasan Pelanggan PT Sun Express - Dharma, Eka Adi; ., Ahyani (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of brand image and relationship marketing on customer satisfaction in the air freight services of PT Sun Express at Soekarno–Hatta International Airport, both partially and simultaneously. The research employed a quantitative associative approach with a population of 946 customers and a sample of 90 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that brand image has a positive and significant effect on customer satisfaction (t = 7.928; sig. = 0.000), as does relationship marketing (t = 9.634; sig. = 0.000). Simultaneously, both variables significantly influence customer satisfaction (F = 130.342; sig. = 0.000). The R Square value of 0.750 shows that 75% of the variation in customer satisfaction is explained by these two variables